Pengembangan Media Teknologi Informasi dalam Pembelajaran Pendidikan Agama Islam - Uli Marfu’ah; Ahmad Faozi (SETYAKI : Jurnal Studi Keagamaan Islam, 2026)
This study aims to analyze the development and utilization of information technology-based learning media in Islamic Religious Education and to identify the supporting and inhibiting factors in its implementation. Islamic Religious Education plays an important role in shaping students’ religious attitudes and their understanding of Islamic values. The research employed a qualitative descriptive approach, collecting data through classroom observation, student questionnaires, and a literature review of relevant academic journals and books. The findings indicate that information technology-based media, such as visual media and interactive multimedia, can increase students’ active participation, enhance their understanding of the material, and create a more engaging and contextual learning environment. Such media also help teachers deliver abstract Islamic Religious Education content more effectively. Nevertheless, several obstacles were identified, including limited facilities and infrastructure, differences in students’ access to technology, and limited instructional time. Therefore, continuous development and optimization of information technology-based learning media are needed to improve the quality of Islamic Religious Education.